Primary Productivity and Mineral Nutrient Status of some Estuarine and Coastal Waters along the East Coast of Peninsular Malaysia during the off Monsoon Period. - Shamsudin, Lokman; Mansor, M. Isa; Husin, Juhari (1984)
A study of the organic and inorganic mineral status, primary productivity and related environmental parameters of some estuarine and coastal waters along the east coast of Peninsular Malaysia indicates that the estuarine waters act as nutrient sources for the adjacent coastal waters. The net photosynthetic values at the estuarine stations ranged from 82.0-125.4 and 104.0-257.9 fJ.g C/1/h while that of coastal stations ranged from 42.0-164.5 and 66.0-198.2 fJ.g C/1/h during the high and low tides respectivelv. During the low tides, at both the estuarine and coastal stations, the dissolved organic nitrogen, particulate orgMlic phosphorus and inorganic ammonium nitrogen were present in high concentrations while that of dissolved oxygen, inorganic nitrate nitrogen and nitrite nitrogen were low throughout the study period.